Penggunaan Media Facebook Bagi Peningkatan Motivasi Belajar Siswa Mata Pelajaran Pendidikan Agama Islam - Marwiah Marwiah (LPPM IAIN Parepare, 2018)
This study aims to determine the use of media facebook on students, and to determine the role of facebook media to increase the motivation to learn PAI students in SMPN 2 Lanrisang. This type of research is descriptive qualitative research. Qualitative method, preferably observation, interview, documentation. This research used Dougherty & Pritchard theory in Bauer. That is Role perception and Role Expectation, with aspect of role: a) Impersonal, b) Working behavior, c) Controlling, d) Behavior change, and e) Various role / activity. The results of this study were: 1) media faceboook has been used in students SMPN 2 Lanrisang, Facebook for the students SMPN 2 Lanrisang not only serves as a social network but has become a medium of learning with the use of group features in facebook media. 2) facebook media contributes to the improvement of students' learning motivation in SMPN 2 Lanrisang, especially on learning of Islamic Religious Education, this is seen among the students who are active in the group facebook PAI